Turbulent flow and heat transfer enhancement of forced convection over heated baffles in a channel Effect of pitch of baffles - Saim, Rachid; Benzenine, Hamidou; Öztop, Hakan Fehmi; Al-Salem, Khaled (Emerald Group Publishing Ltd, 2013)
Purpose - The purpose of this paper is to examine the turbulent fluid flow and heat transfer characteristics for rectangular channel provided with solid plate baffles which are arranged on the bottom and top channel walls in a periodically staggered way. Design/methodology/approach - The turbulent governing equations are solved by a finite volume method with the second-order up winding scheme and the k-omega turbulence model to describe the turbulent structure. The velocity and pressure terms of momentum equations are solved by SEMPLE (semi-implicit method for pressure-linked equation) algorithm. The parameters studied include the entrance Reynolds number Re (5.10(3)-2.10(4)), the baffles height are fixed at (h = 0.08 m); whereas three different baffle spacing were considered S-1 = D, S-2 = D/2 and S-3 = 3D/2 and the working medium is air. Findings - In this work, it is found that vortex shedding generated by the baffle on the upper wall can additionally enhance heat transfer along the baffle surfaces. The wavy flow significantly changes the recirculating zone behind the last baffle. Finally, changing the baffles spacing seemed to reduce to changing the heat transfer surface between the solid and the fluid in the sense that higher heat transfer is obtained for lower spacing between baffles. Originality/value - The results of the numerical calculations of the flow field indicate that the flow patterns around the solid baffles depending on the spacing of the baffles and it significantly influences the local heat transfer coefficient distributions. The problem is inversely proportional for the friction factor.
Keywords: Plate baffles; Channel; Turbulent flow; Numerical solution; Forced convection; Flow; Heat transfer